2020
DOI: 10.1007/s11357-020-00170-8
|View full text |Cite
|
Sign up to set email alerts
|

Advances in cytomegalovirus (CMV) biology and its relationship to health, diseases, and aging

Abstract: Cytomegalovirus (CMV) is one of the largest and most ubiquitous latent persistent viruses. Most humans are infected with CMV early in life, and all immunocompetent humans spend several decades living with CMV. In the vast majority of the hosts, CMV does not cause manifest disease, and CMV therefore can be considered part of normal aging for 50-90% of the human population worldwide. Experimental, clinical, and epidemiological studies suggest that CMV carriage can have nuanced outcomes, including both potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Our results suggest that CMV discordance increases immune diversity between twins (Fig. 3 ), showing that a large set of immune cells are impacted by CMV, as previously publications have found [ 26 , 28 , 32 ]. Twin-twin averaged immunological distances were significantly lower than non-twin distances for both CMV concordant positive and CMV concordant negative twins, but not between CMV discordant twins (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results suggest that CMV discordance increases immune diversity between twins (Fig. 3 ), showing that a large set of immune cells are impacted by CMV, as previously publications have found [ 26 , 28 , 32 ]. Twin-twin averaged immunological distances were significantly lower than non-twin distances for both CMV concordant positive and CMV concordant negative twins, but not between CMV discordant twins (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Human CMV is a prevalent latent virus that has been found to shape significant portions of the immune system, altering the frequency, phenotype, and potential function of important immune cell groups [ 26 32 ]. The underlying mechanisms behind these relationships are not well studied, but suspected to be a result of memory inflation pathways [ 27 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that CD8 + T sen accumulate in older humans and that this is largely driven by ongoing sub‐clinical responses to persistent viruses especially cytomegalovirus (CMV) (Jackson et al, 2017; Nikolich‐Žugich et al, 2020; Savva et al, 2013). Moreover, this population has increased capacity to rapidly respond to signals mediated by inflammatory cytokines (Freeman et al, 2012).…”
Section: Cd8+ Tsen Accumulate During Ageing and Persistent Viral Infementioning
confidence: 99%
“…Both pediatric cases met the symptomology of possible autoimmune encephalitis, which was supported by their laboratory results (4). ANNA-2 is the most common intracellular neuronal antibody marker (5). Furthermore, classic opsoclonus-myoclonus syndrome, psychosis, dyskinesia, and weakness can be the presenting features of ANNA-2-related autoimmune encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…The rst question of interest is how and why ANNA-2, a well-known paraneoplastic antibody, was present without cancer in pediatric patients. It is well known that CMV and HSV can lie latent in the mucosa and neurons (5,6). Consequently, recent studies have indicated that an imbalance between immunomicrobiology and the immune system could impair the quality of life in the elderly (7), and immune dysregulation in post-HSV encephalitis could cause autoimmune encephalitis (8).…”
Section: Discussionmentioning
confidence: 99%